The Effect of Work Environment, Career Development, and Extrinsic Motivation on Job Satisfaction of Diy Transportation Service Employees - Yosepina Winarni; Ignatius Soni Kurniawan (Jurnal Ilmu Manajemen Profitability, 2022)
The purpose of this study was to determine the effect of the work environment, career development, and extrinsic motivation on employee job satisfaction at Dinas Perhubungan Daerah Istimewa Yogyakarta (DIY). This research method uses multiple linear regression analysis to analyze the effect of the independent variable on the dependent variable in the study. The population in this study were all employees at Dinas Perhubungan DIY, with a sample size of 50 respondents. The results of the study stated that the work environment, career development, and extrinsic motivation had a positive and significant influence on employee job satisfaction